2018
DOI: 10.1089/sur.2018.029
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Operative Nasal Eradication Therapy PreventsStaphylococcus aureusSurgical Site Infections in Aortoiliac Surgery

Abstract: We conclude that S. aureus nasal screening and eradication with mupirocin and chlorhexidine reduces S. aureus SSI and its complications after aortoiliac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…55 Of note, S. aureus eradication in this setting was associated with a decrease in S.aureus related SSIs but not in the SSIs due to other bacteria, which may be explained by the competing behaviour of bacteria causing SSI. 55…”
Section: Logistics and Peri-operative Carementioning
confidence: 75%
See 2 more Smart Citations
“…55 Of note, S. aureus eradication in this setting was associated with a decrease in S.aureus related SSIs but not in the SSIs due to other bacteria, which may be explained by the competing behaviour of bacteria causing SSI. 55…”
Section: Logistics and Peri-operative Carementioning
confidence: 75%
“…The incidence of S. aureus SSI was significantly lower in patients who were screened positive and who were treated for methicillin resistant S. aureus (MRSA) nasal carriage compared with patients negative for nasal MRSA carriage (0% vs. 13.6%). 55 In addition, both 30 day mortality reintervention rates were significantly lower in the treated group (1.3% vs. 13.6%). 55 Of note, S. aureus eradication in this setting was associated with a decrease in S.aureus related SSIs but not in the SSIs due to other bacteria, which may be explained by the competing behaviour of bacteria causing SSI.…”
Section: Logistics and Peri-operative Carementioning
confidence: 83%
See 1 more Smart Citation
“…It is commonly present as part of the normal flora of the skin and nose, with screening studies reporting carriage rates of around 20%. 146 An association between nasal carriage of Staphylococcus aureus and the development of SSI has been recognised. 147 Consequently, identification of nasal carriage before surgery and treatment of positives with a 5-day course of mupirocin and chlorhexidine soap has been associated with a significant reduction in rate of SSI caused by Staphylococcus aureus.…”
Section: Nasal Decolonisationmentioning
confidence: 99%
“…Of the various sites reported, the nose is considered to be an important reservoir in humans and nasal colonization has been reported to be an independent risk factor for SSIs (7)(8)(9). To reduce the incidence of S. aureus infections, nasal application of topical mupirocin has been widely reported in the literature (10,11). In one of the earliest randomized controlled trials (RCTs) on surgical patients, Bode et al (12) reported a significantly reduced incidence of SSIs in S. aureus carriers with the use of pre-operative nasal mupirocin and chlorhexidine soap.…”
Section: Introductionmentioning
confidence: 99%